Evaluation of self-medication patterns among under-graduate medical students of Adichunchanagiri institute of medical sciences, Karnataka, India: a cross-sectional questionnaire-based study - Shivamurthy, Shwetha; Manchukonda, Ravi Shankar; Gurappanavar, Deepika (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Self-medication is the treatment of common health problems with medicines that are taken on patient's own initiative or on advice of a pharmacist, without professional supervision. It is now becoming a common practice in many countries mainly due to lack of access to health care, easy availability of OTC (over the counter) drugs in market and poor drug regulatory practices. It assumes special significance among medical students as they are aware of the available medications. Methods: A cross-sectional questionnaire based study was done from among undergraduate medical students, Adichunchanagiri institute of medical sciences (AIMS), BG Nagar, Karnataka, India. A structured questionnaire was given to medical students of all 4 years. Consent was taken from the students. Results: Our results showed that 66% of the AIMS undergraduate students practiced self-medication. Paracetamol (40.8%) was the most common self-medicated drug followed by antihistaminics (20.2%), antimicrobial drugs (8.1%), analgesics (7%) and others. Fever (33.2%) was the most common illness for opting self-medication followed by upper respiratory tract infection (23.1%), headache (17%), allergy (6.64%), diarrhea (6.3%), menstrual pain (2.53%) and others. Most common reason for opting self-medication was the illness being too trivial. Conclusions: The prevalence of self‐medication among medical students is high, facilitated by the easy availability of drugs and information from textbooks or seniors. A significant number of students were unaware of the adverse effects of the medications that they themselves take and suggest to others. Therefore, potential problems of self‐medication should be emphasized to the students.